Heterogamy and contraceptive use among married and cohabiting women. (September 2022) - Jacobs, Josephine C.; Stanfors, Maria
Abstract: Decisions about which contraceptives to use are a key component of a couple's "fertility work, " and these decisions can be made in homogamous or heterogamous couple contexts. Relative resource theory and the strain perspective suggest that heterogamy may lead to differences in bargaining power or higher levels of discordance within couples, thereby affecting the distribution of fertility work and decisions about which contraceptives a couple will use. While heterogamy has been linked to less effective contraceptive use amongst teenagers, its role in the contraceptive behavior of married and cohabiting women has been less widely studied. This study examines the association between relationship context in terms of education, age, and race/ethnicity heterogamy and partnered women's use of contraceptives. We used data on partnered women aged 20–45 who were trying to avoid pregnancy from the 2006–2015 National Survey of Family Growth (n = 8097). We used multinomial logistic regressions to determine whether education, age, or race/ethnicity heterogamy was associated with the use of male or female sterilization, long-acting reversible contraceptives (LARCs), other hormonal contraceptives, or other non-hormonal methods. We did not find consistent evidence that relative bargaining power due to higher education, more advanced age, or racial/ethnic privilege resulted in the use of methods requiring lower levels of fertility work. We found some evidence supporting the strain perspective. Younger women (20−34) who differed from their partners along two or more dimensions were less likely to use contraceptive methods requiring ongoing effort and coordination (i.e., LARCs, other hormonal methods, and non-hormonal methods). This association was not observed among women aged 35–45. Despite the more permanent nature of marriage/cohabitation, differences between partners in heterogamous relationships may factor into the contraceptive decision-making process, especially among younger adults at earlier stages of their relationships. Highlights: Couple composition shapes contraception work across the reproductive life cycle. Among younger adults, education, age, and race/ethnicity heterogamy are associated with contraceptive decision-making. Women (20-34) in couples differing along ≥2 dimensions were less likely to use contraceptives needing ongoing fertility work. Research is needed to understand whether this association among younger women is due to increased relationship strain. Contraceptive programs focusing on the couple context – among both adolescents and adult partnered women and men – are needed.